Simplify: (7x2 − 8x − 4) + (−2x2 + 3x + 5) + (5x2 − 10x − 8) a 10x2 + 15x − 7 b 10x2 + 5x − 7 c 10x2 − 15x − 7 d 10x2 − 15x − 9

QUESTION POSTED AT 29/05/2020 - 01:12 AM

Answered by admin AT 29/05/2020 - 01:12 AM

7x^2 - 8x - 4 + (-2x^2 + 3x + 5) + 5x^2 - 10x - 8 =
7x^2 - 8x - 4 - 2x^2 + 3x + 5 + 5x^2 - 10x - 8 =
10x^2 - 15x - 7 <==
Post your answer

Related questions

The expression 3 × 7 – 4 × 8 + 2 is equivalent

QUESTION POSTED AT 02/06/2020 - 01:42 AM

9000 for 5 years at 4.5% compounded monthly

QUESTION POSTED AT 02/06/2020 - 01:30 AM

Graph the exponential function. y = 4(3) x

QUESTION POSTED AT 02/06/2020 - 01:30 AM